Effects of testosterone and vitamin E on the antioxidant system in rabbit testis - Aydilek, N; Aksakal, M; Karakilçik, AZ (Wiley, 2004)
The aim of the study was to investigate the effects of testosterone propionate and vitamin E on the antioxidant system in the testis. Thirty-two male New Zealand White rabbits were randomly divided into four groups. The first group was used as control. The second group was injected with testosterone propionate, the third group vitamin E and the fourth group vitamin E and testosterone propionate combination. All treatments were carried out during 6 weeks and oxidative parameters were evaluated in homogenized testicular tissue. The levels of vitamin E and the activity of glutathione peroxidase were lower (P < 0.05) in the testosterone group than in controls. However, vitamin C and malondialdehyde levels were higher (P < 0.05) in this group than in controls. The levels of reduced glutathione, beta-carotene, vitamin C and E increased, but malondialdehyde levels decreased in the vitamin E group, when compared with controls (P < 0.05). Vitamin E and beta-carotene levels were significantly higher (P < 0.05) in the combination group than in testosterone group. However, MDA levels were lower (P < 0.05) in combination group than in the testosterone group. In conclusion, administration of testosterone propionate led to a significant elevation of oxidative stress. Vitamin E is quite an effective antioxidant which protects rabbit testis against lipid peroxidation, and, testosterone-induced lipid peroxidation could be improved by additional vitamin E treatment.
Keywords: antioxidants; lipid peroxidation; rabbit; testis; testosterone